AJARAN PEMBEBASAN DALAM LONTAR SANGHYANG MAHÃJÑANA - Ida Made Windya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
One source of Śiva’s teachings is Sanghyang Mahãjñana, the kind of śāstra tattwa . Tattwa refers to the core meaning or essence. Tat refers to the existence of God, that is, He is the absolute Bhatāra-soul. Twa is an affirmation as well as an affirmation of the existence of him who is as the Most and transcends the senses. Tattwa Sanghyang Mahãjñana is the essence of great liberating knowledge, teachings that give directions to enter the realm of Śunya or Śiwa. The teachings of Tattwa Sanghyang Mahājñana, discussed in this article include, the concept of liberation, namely the liberation of the soul, the union of the universe with the universe, and the loss of the attachment of the soul to the body is often referred to as release, and the path of liberation and stages of liberation in the Sanghyang Mahājñana include; this initial stage is the stage to uncover the secrets of human beings, the core stage is the stage of inner training to realize the teachings contained in the Sanghyang Mahājñana texts that have been occupied so far in order to achieve the highest goal of life, and the final stage which is the process of Sanghyang atma's journey. in the body going outside the body to achieve liberation from the bond of the material elements and the circle of birth-life-death that has shackled it, and re-integrates with its source, namely Śiva.